2021
DOI: 10.1016/j.resinv.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of combination therapy with baricitinib, remdesivir, and dexamethasone in patients with severe COVID-19

Abstract: Background Coronavirus disease 2019 (COVID-19) has spread worldwide and is also an important disease in Japan. Thus, the optimal treatment strategy for severe COVID-19 should be established urgently. The effects of combination treatment with baricitinib—a Janus kinase inhibitor, remdesivir, and dexamethasone (BRD) are unknown. Methods Patients who received combination therapy with BRD at the Japanese Red Cross Medical Center were enrolled in the study. All patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…The results of the clinical trial of baricitinib in combination with remdesivir (NCT04401579) revealed superior activity in reducing the recovery period compared to remdesivir alone [ 92 ]. Similar results were also obtained when using a combination of dexamethasone with baricitinib/remdesivir [ 93 ]. Finally, the combination of baricitinib and remdesivir received an Emergency Use Authorization (EUA) from the FDA to treat hospitalized patients with COVID-19.…”
Section: Introductionsupporting
confidence: 81%
“…The results of the clinical trial of baricitinib in combination with remdesivir (NCT04401579) revealed superior activity in reducing the recovery period compared to remdesivir alone [ 92 ]. Similar results were also obtained when using a combination of dexamethasone with baricitinib/remdesivir [ 93 ]. Finally, the combination of baricitinib and remdesivir received an Emergency Use Authorization (EUA) from the FDA to treat hospitalized patients with COVID-19.…”
Section: Introductionsupporting
confidence: 81%
“…In Izumo et al , 53 an observational study of 44 patients with severe COVID-19 received triple therapy of BNB (4 mg daily oral), RMD (IV 200 mg loading, 100 mg maintenance daily) and DMS (oral or IV 6 mg daily). It was found that patients who received BNB had a low mortality rate (2.3%) and decrease in mechanical ventilation requirement (90%) with approximately 34% adverse events observed.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that patients who received BNB had a low mortality rate (2.3%) and decrease in mechanical ventilation requirement (90%) with approximately 34% adverse events observed. 53 …”
Section: Resultsmentioning
confidence: 99%
“…Previously, Izumo et al. reported that triple therapy was effective with 2.3% mortality rate [6] . Thus, the add-on efficacy of baricitinib was expected in hypoxic patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%